F-27 ИЗОХИНОЛИН АЛКАЛОИДИНИНГ МИОКАРД ҚИСҚАРИШИ ФАОЛЛИГИГА ТАЪСИР МЕХАНИЗМИНИ ТАВСИФЛАШ Ш.Б.Қурбонова –тадқиқотчи - Жумаев, И.З.; Бобоев, С.Н.; Усманов, П.Б.; Есимбетов, А.Т.; Жўрақулов, Ш.Н. (SCIENCE and SOCIETY, 2022)
To date, the search for new pharmacological methods for the prevention and treatment of diseases of the cardiovascular system is one of the urgent problems of modern pharmacology and medicine. Of particular interest is the fact that isoquinoline alkaloids currently have a pronounced antiarrhythmic effect. In our studies, it was found that the isoquinoline alkaloid F-27 has a negative inotropic effect on the contractile activity of the papillary muscle of the rat heart. It has been proven that the negative inotropic effect of this alkaloid is partly due to the blockade of Ca2+-channels. Experiments with lidocaine show that the negative inotropic effect of the F-27 alkaloid is mainly due to the blocking of Na+-channels.